Reduction in circulating level of HMGB-1 following continuous renal replacement therapy in sepsis. (July 2016) - Ueno, Takuya; Ikeda, Toshiaki; Yokoyama, Takayoshi; Kihara, Yu; Konno, Osamu; Nakamura, Yuki; Iwamoto, Hitoshi; Shimizu, Tetsunosuke; McGrath, Martina M.; Chandraker, Anil
Highlights: CHDF treatment maintained imbalanced temperature and modulated increased HMGB-1 levels. HMGB-1 modulation by PMX-DHP can be enhanced with using CHDF in sepsis. There is a clear correlation between body temperature and HMGB-1 levels. Cytokine modulation with Thermoregulation by CRRTs in sepsis. Abstract: Early recovery from shock improves prognosis in patients with severe sepsis and septic shock. During this period, cytokine imbalances mediate the development of organ damage and mortality. In Japan, we have access to hemoperfusion using an immobilized polymyxin B fiber column for endotoxin removal (PMX-DHP) and continuous hemodiafiltration (CHDF) as artificial support for patients with septic shock, with the aim of improving hemodynamics and organ dysfunction caused by elevated inflammatory cytokines and mediators. In this Short communication, we discuss recent findings showing anti-inflammatory treatment following these continuous renal replacement therapies in sepsis.